2022
DOI: 10.1308/rcsann.2021.0205
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of emergency laparoscopy in the elderly

Abstract: Introduction This paper assessed the association between operative approach and postoperative in-hospital mortality in elderly patients undergoing emergency abdominal surgery. Patients undergoing emergency laparotomy have high morbidity and mortality rates. One-third of patients requiring emergency surgery are over 75 years old, and their in-hospital mortality rate exceeds 17%. Fewer than 20% of emergency abdominal operations in the UK are attempted laparoscopically, and only 10% are completed laparoscopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several tools exist to identify frailty in emergency cases, and in a simplified approach, previously, we revealed that low psoas muscle volume predicted early postoperative functional decline [ 32 ]. In addition, recent studies have shown that the use of laparoscopy in emergency abdominal surgery demonstrates a significant reduction in mortality in frail older patients [ 33 ]. This study found that LS, compared to OS, was less likely to be statistically associated with a postoperative functional decline in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools exist to identify frailty in emergency cases, and in a simplified approach, previously, we revealed that low psoas muscle volume predicted early postoperative functional decline [ 32 ]. In addition, recent studies have shown that the use of laparoscopy in emergency abdominal surgery demonstrates a significant reduction in mortality in frail older patients [ 33 ]. This study found that LS, compared to OS, was less likely to be statistically associated with a postoperative functional decline in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An EGS care model is but one of many innovations, which is changing the paradigm of emergency surgical care. There is significant evidence pointing toward other modifiable factors such as laparoscopy, 14,16 particularly in the elderly, 32 that can result in improved outcomes in this high-risk cohort of emergency patients. Evidence from the United States points toward improved outcomes in hospitals that have dedicated acute surgery units, with important factors cited such as improved access to emergency theaters and interventional services such as radiology 6,7,10,30 .…”
Section: Discussionmentioning
confidence: 99%